Molecular identification of genetically modified castor bean (Ricinus communis) plants : first approximation (2018)
A genetic transformation protocol mediated by ​Agrobacteriumtumefaciens was carried out in castor bean epicotyls (​Ricinus communis) by researchers from CIBIOP research group (Biological Sciences and Bioprocesses) at Universidad EAFIT. ​Ricinuscommunisseedlings were infected with strain LBA4404, which contained the binary vector pCAMBIA1305.2 which in turn had the genetic cassette ​CAM 35S-fatty acid hydroxylase (FAH12) - NOS terminator. For the transformed plants a selection medium was establis hed with respective concentrations of antibiotics such as hygromycin and cefotaxime. Seeking to verify the presence of inserts in genetically modified plants, DNA wasextractedfromthenewleaves from transformed epicotyl, for further analysis by conventional PCR. For DNA analysis, two tests were carried out, in which the PCRs of the​hptII and the​opt-FAH12 genes were standardized for their subsequent monitoring. Finally, as a confirmatory test, the obtained amplicons were sequenced by Sanger. The previously developed protocolisa relevant step to achieve a solid molecular characterization path looking forward to get a high efficient method to transform a tropical variety of ​Ricinus.